The Role of School Counselors in Responding to Students' Psychological Wellbeing Post-Parents' Divorce - Rustianti, Nora; Fitriani , Wahidah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
The occurrence of divorce between parents often has a negative impact on the psychological well-being of teenagers, such as the emergence of feelings of anxiety, stress, and even decreased self-confidence. Guidance and Counseling Teachers have a strategic role in providing emotional support and helping students to overcome the psychological impacts that arise. This research aims to identify the role of Guidance and Counseling (BK) teachers in supporting the psychological well-being of adolescents after their parents' divorce. This research uses qualitative methods with literature review techniques. The research results show that the interventions carried out by guidance and counseling teachers include identifying and helping students manage emotions, providing support in crisis situations, assisting in developing social skills and providing space for expression, as well as creating a supportive environment for students. This means that guidance and counseling teachers have a crucial role in supporting students' psychological well-being conditions after experiencing their parents' divorce.